Sports policy in the face of forced recruitment (2021)
This work aims to analyze the management of sport as a prevention alternative for the forced recruitment of minors in the Metropolitan Area of the Aburrá Valley (Colombia) and its reinvention in the context of Covid-19. However, although this is a problem affecting the 10 municipalities that make up it, there is a lack of coordination and articulation of sports policy at the metropolitan level for intervention from the intermunicipal level. The research used a qualitative approach under the method of informed theory, the understanding of which was made through the technique of documentary analysis and semi-structured interviews systematized in a matrix of documentary analysis. The results yielded low administrative capacities of public authorities of municipal sport, fragmentation of local governance and recently managed scenarios for the metropolitan articulation and coordination of sports policy. It is concluded that there is an invisibilization of the sport sector as an instrument for the prevention of forced recruitment of minors from the gaze of municipal and inter-municipal security and coexistence agencies, lack of local synergy for the coordination of joint purposes and the G10 and the Bureau of Coordinators of the southern area are presented as recent scenarios of metropolitan governance under the context of covid-19.